EKSPRESORIA - Arif Hutria; Esy Maestro; Yensharti Yensharti (FBS Universitas Negeri Padang, 2013)
Abstract The idea in this artwork was started from the expression of feeling which is channeled into expression. Then, this expression was expressed into musical compositions that is interpreted in tones of melody, harmony, and rhythm that is composed into musical expression of feeling. This artwork was created by implementing some artwork methodologies; they were exploration, document analysis, experiment, and formation phase. This musical composition was also done in 3 parts of composition, namely Part A, Part B, and Part C. The Part A shows a calm expression in happiness. Then, Part B brings “conflicts or problems